Reading habits & reading characters of TESL teacher trainees : a case study of UiTM Shah Alam / Nur Atiqah Jalaludin - Jalaludin, Nur Atiqah (Faculty of Education, 2014)
Reading habit is the frequency of one reading any reading materials while reading character is the set of qualities posses by a reader. Cox and Schaetzel confined reading characters into three categories namely prolific, functional and detached. Based on literature it seems that there is a possible link between these two variables. Hence, this study aimed to investigate the reading habits and reading characters of TESL teacher trainees of UiTM Shah Alam, Malaysia. Guided by three research objectives and three research questions, this study intended to investigate the reading habits and reading characters of the TESL teacher trainees. In addition, it is also aimed to determine the justifications for the teacher trainees perceived reading characters. This study has employed the mixed-methods research design consisting of both qualitative and quantitative procedures in gathering and analyzing the data. 57 respondents were chosen among the final year TESL teacher trainees. The findings revealed that firstly, the teacher trainees read online materials most frequently compared to other reading materials. Secondly, it was recorded that a majority of the teacher trainees perceived themselves as functional rather than detached and prolific readers. Lastly, the justifications given by the teacher trainees seemed to corroborate the quantitative data analysis. Thus, discussion, implications and recommendations for future research were also presented to conclude the study.